Pengaruh Kepemimpinan Terhadap Motivasi Kerja Pegawai Pada Kantor Pengelolaan Sumber Daya Air Pajalele Kecamatan Tanasitolo Kabupaten Wajo - Burhanuddin Burhanuddin; Maspawati Tokang (Journal of Management and Creative Business, 2024)
Leadership is sometimes understood as the power to move and influence people. Leadership is a tool, means or process for persuading people to be willing to do something voluntarily/joyfully. There are several factors that can move people, namely threats, rewards, authority and persuasion. Leaders establish cooperative relationships with the people they lead. Thus, all work programs will be carried out thanks to the help of the people they lead, because it is impossible for each leader to work alone, and it is impossible to act with his power to order other people to work solely for himself.